Functional analysis of the BEige and Chediak-Higashi domain gene MpSPIRRIG in Marchantia polymorpha - Koebke, Eva; Stephan, Lisa; Stetter, Markus G.; Hülskamp, Martin (Frontiers in Plant Science, 2022)
BEACH domain containing proteins (BDCPs) have been described to function in membrane-dependent processes in eukaryotes. This role was also observed for the BDCP SPIRRIG (SPI) in the model plant Arabidopsis thaliana in the context of cell morphogenesis. Additionally, AtSPI was found to control salt stress resistance by mediating mRNA stability and salt stress-dependent processing body formation. In this work, we utilize an evolutionarily comparative approach to unravel conserved, basal BDCP functions in the liverwort Marchantia polymorpha. Our phenotypic and physiological analyses show that MpSPI is involved in cell morphogenesis and salt resistance regulation, indicating that both functions are evolutionarily conserved between the two species. Co-localization was found with endosomal and P-body markers, suggesting links to membrane-dependent processes and mRNA metabolism. Finally, we present transcriptomics data showing that AtSPI and MpSPI regulate orthologous genes in A. thaliana and M. polymorpha.